Understanding Why a Ground Combat Vehicle That Carries Nine Dismounts Is Important to the Army - Held, Bruce J. (RAND Corporation, 2013)
For over 50 years, the Army has tried to develop and field survivable, lethal infantry fighting vehicles (IFVs). The Ground Combat Vehicle is an attempt to provide the infantry with an IFV that can carry a full infantry squad of nine men capable of dismounting under fire and defeating the enemy in complex terrain.